TEACHING SPEAKING THROUGH (IGA) INFORMATION GAP ACTIVITY AT TENTH GRADE OF MAN 4 KARAWANG - Robiatul Adawiah; Nuraen Nuraen (PROJECT (Professional Journal of English Education), 2018)
Speaking is the one of language skill that is used in communication to deliver the intention of utterances. speaking is an activity that can not be separated with teaching and learning process. speaking has become a skill that should be owned by teacher. Information gap activity is the activity that each student have different information that should be completed with exchanging the information with their friend because there is a gap between the information. The objective of the research is whether information gap activity effective to the students’ speaking ability. The writer used quantitative research design and for the method is pre-experimental method. The participants of the research is X IPA 2 of MAN 4 Karawang consist of thirty two students. The data conducted through pretest and posttest and computed using SPSS 24. The result of the test is effective. From the normality of distribution test, the result of the test is normal, significance value on Kolmogrov Smirnov is 0.078 on pretest and 0.073 on posttest. It means the data is normally distributed because the value is higher than 0.05. The result of significance value is 0.312 it is higher than 0.05, as a result the test is homogen. Beside that, in one sample t-test, the result of significance two tailed is 0.000 and lower than 0.05. from the data above, it can be concluded that the null hypothesis of this research that is “Information gap activity is not effective to teach speaking” is rejected. In other word, it was proven that teaching speaking using information gap activity is effective to be used by teacher.Key words: Speaking, Information gap.